PENERAPAN METODE WATERFALL PADA PENGEMBANGAN SISTEM INFORMASI PEMESANAN PAKET DEKORASI - Yohana Sinarty Jahang; Atik Nurmasani; Marwan Noor Fauzy; Azis Catur Laksono (Universitas Amikom Yogyakarta, 2025)
Linia Decoration is a business that provides decoration services for various events, including engagements, weddings, and other special occasions. Currently, Linia Decoration faces major challenges in the ordering process, which still relies on direct interaction and WhatsApp social media. Management has difficulty scheduling meetings with customers and responding to customer messages in a timely manner. The development of a website-based ordering information system, utilizing the Waterfall method, was implemented to address these issues. The development steps consist of data collection and needs analysis, system design, program code writing, and system testing. The results of the study indicate that the development of the decoration package ordering information system can be realized according to functional requirements. Black box testing shows that all features can run well